Factors Affecting Patient Response Time in the Emergency Department at Puri Husada Tembilahan Regional Hospital, Indragiri Hilir Regency, Riau - Syufriyadi DS; Nuraini Nuraini; Ismail Efendy (PROMOTOR, 2026)
The Emergency Department (ED) is a hospital unit responsible for managing patients with emergency and life-threatening conditions, requiring a fast and accurate response time. However, the response time performance at the Emergency Department of RSUD Puri Husada Tembilahan has not been optimal. Data from January to March 2025 showed that out of every 10 patients, only 6–7 patients (60–70%) received treatment within the standard response time (0–10 minutes for red category, 30 minutes for yellow, and 60 minutes for green), while 3–4 patients (30–40%) did not meet the standard. This study aimed to analyze the factors influencing patient management response time in the Emergency Department of RSUD Puri Husada Tembilahan, Indragiri Hilir Regency, Riau. This study employed a mixed-methods approach with a quantitative sample of 40 nurses selected from a population of 66 using the Slovin formula, and 5 qualitative informants (2 physicians and 3 nurses). Data were collected through questionnaires, in-depth interviews, and observation. Quantitative data were analyzed using univariate, bivariate, and multivariate analyses with multiple logistic regression, while qualitative data were analyzed descriptively. The results showed that knowledge, skills, facilities, and training had a significant influence on patient management response time in the ED, with knowledge identified as the most dominant factor. Meanwhile, motivation, workload, and patient condition were not significantly associated with response time. In conclusion, knowledge, skills, facilities, and training are key factors influencing response time in emergency patient management. It is recommended that hospitals enhance healthcare workers’ competencies through regular and structured training and ensure adequate facilities and infrastructure to improve the quality of emergency services.